Evaluation of the QIAGEN 140-SNP forensic identification multiplex from latent DNA using massively parallel sequencing. (29th July 2019) - Young, J. M.; Martin, B.; Linacre, A.
ABSTRACT: Direct PCR can be used to successfully generate full STR profiles from latent DNA. However, some substrates have been shown to be more problematic and in some cases only partial profiles are recovered. As latent DNA is present on the surface of objects in very low quantity, and potentially low quality, the fragment lengths targeted by STR typing may be too large to successfully amplify all markers. As an alternative, QIAGEN have developed a 140-SNP multiplex that targets much shorter amplicons and generates extremely low probabilities of any two unrelated individuals having identical genotypes. Here, we present the first forensic identification SNP data from latent DNA using massively parallel sequencing. We applied the QIAGEN 140-SNP forensic identification multiplex to swabs collected from multiple substrates (including mobile phone, fingerprint, wire, zip-lock bag and SIM card) and multiple donors.